2000
DOI: 10.1046/j.1365-2044.2000.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on postoperative nausea and vomiting

Abstract: SummaryIn an attempt to quantify the postoperative effects of smoking, 327 consecutive patients undergoing arthroscopic day case knee surgery were given a standard anaesthetic consisting of an intravenous induction with propofol and fentanyl followed by inhalational maintenance using isoflurane in an oxygen and nitrous oxide mixture. Pre-operatively, patients were asked inter alia to give details of social smoking habits. Postoperatively, patients were given standard analgesic and anti-emetic drugs. Prior to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 26 publications
4
31
0
2
Order By: Relevance
“…25,112 Interestingly case reports have suggested that human smokers require higher doses of propofol to achieve anesthesia and experience less postanesthesia side effects than nonsmokers. 113,114 This is consistent with a role for elevated brain CYP2B6 seen in smokers, resulting in faster inactivation of propofol in the brain.…”
Section: Drug Efficacysupporting
confidence: 81%
“…25,112 Interestingly case reports have suggested that human smokers require higher doses of propofol to achieve anesthesia and experience less postanesthesia side effects than nonsmokers. 113,114 This is consistent with a role for elevated brain CYP2B6 seen in smokers, resulting in faster inactivation of propofol in the brain.…”
Section: Drug Efficacysupporting
confidence: 81%
“…For example, brain CYP2B6 protein levels are higher in smokers compared to nonsmokers (Miksys et al, 2003), whereas hepatic levels are unchanged (Hesse et al, 2004), suggesting that smokers may have different therapeutic responses or side effects to CYP2B6 substrates. The anesthetic propofol is inactivated by CYP2B6, and there is evidence that smokers require a larger dose of propofol (Lysakowski et al, 2006) and report fewer postoperative side effects (Chimbira and Sweeney, 2000). Alterations in brain CYPs that activate or inactivate neurotoxins may affect an individual's risk for neurotoxicity from a particular xenobiotic.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what others have found that non-smoking status is a risk factor for post operative nausea and vomiting. In a study by Chimbira it was noted that those who did not smoke were more likely to develop postoperative nausea and vomiting [12].…”
Section: Discussionmentioning
confidence: 99%